Production/operations management : quality, performance, and value - Evans, James R. (James Robert), 1950- (St.Paul, MN : West, 1997)
Foundations of P/OM 1. Strategic issues in operations. Designing and managing production processes. Managing materials. Planning and scheduling.
Keywords: Management; Production; Factory; Production management; Factory management